Efforts to Improve Religious Tolerance Attitudes Through Islamic Religious Education Learning Based on Interfaith Dialogue to Improve Harmony Between Students at SMA Negeri 1 Barumun - Siregar, Zulham Efendi; Nasution, Mhd Arif (MANDAILING GLOBAL EDUKASIA, 2024)
This Classroom Action Research (CAR) focuses on evaluating the effectiveness of implementing interfaith dialogue in Islamic Religious Education (PAI) to improve attitudes of religious tolerance and build social harmony in SMA Negeri 1 Barumun. This research was conducted in two cycles, with data collection through pre-test and post-test, observation, interviews, and reflection journals. The results showed that the implementation of interfaith dialogue significantly improved students' understanding of religious tolerance. This initiative also encouraged increased empathy and respect for peers from different religious backgrounds, as students engaged in meaningful and respectful discussions. The role of the teacher as a facilitator is very important in creating a safe and supportive atmosphere for dialogue, so that discussions can be productive and inclusive. In addition, the use of reflection journals helped students to internalize their experiences and encouraged self-reflection. These findings suggest that interfaith dialogue in religious education has an important role in creating a more inclusive and harmonious school environment. This approach has proven to be an effective strategy in promoting religious tolerance and mutual respect within a diverse community. This study emphasizes the importance of integrating inter-religious dialogue into educational programs to foster tolerance and understanding in society.